Implementasi Pendekatan Realistic Mathematics Education (RME) dengan Media Pembelajaran Pantar Berbantu QR Code untuk Meningkatkan Hasil Belajar Matematika - Agustina, Nining; Jatmiko; Lestari, Dwi Puji (PTK: Jurnal Tindakan Kelas, 2025)
This research is motivated by the problem of low understanding of mathematical concepts indicated by low learning outcomes and student participation. To determine the activity and learning outcomes after the application of the QR Code-assisted RME approach to mathematics learning on flat shape material. This research is a PTK involving grade IV students as subjects. Data were collected through direct observation and assessment of learning outcomes, then analyzed using a quantitative descriptive approach. The findings of this study indicate that the implementation of the Realistic Mathematics Education (RME) approach with PANTAR learning media assisted by QR Code can increase student activity. Meanwhile, learning outcomes also increased, from 63.64 to 95.45%. The learning approach applied has been proven to increase participation and mathematics learning outcomes. Therefore, the use of Realistic Mathematics Education (RME) with PANTAR media assisted by QR Code can be an effective choice for teachers to create more interesting and varied learning.